PENGARUH CEKAMAN ABIOTIK TERHADAP EKSPRESI GEN DAN KONSENTRASI METABOLIT SEKUNDER PADA Catharanthus roseus - Nur Ahmad Rudin (Jurnal Pro-Life, 2020)
Catharanthus roseus is a medicinal plant that widely known as an important pharmaceutical source through secondary metabolites, especially Indole Alkaloid Terpenoid (TIA) with vincristine and vinblastine in the treatment of cancer. Primary and specific metabolisms are closely related. Primary metabolism plays a role in providing precursors to secondary metabolism. Environmental stress can reduce the productivity of primary metabolites and increase secondary metabolite products. The effect of increasing secondary metabolic activity will increase the quality and efficacy of plant simplicia drugs. Based on this, environmental stress plays a role in increasing the induction and concentration of certain secondary metabolites in plants. This review aims to determine the effect of abiotic stress on secondary metabolite concentrations in C. roseus. The results showed that primary and secondary metabolites in plants are interrelated because primary metabolites in plants can serve as precursors and signals for synthesis of secondary metabolite. Molecular understanding of these interconnections is important as a novel metabolic engineering approach to enhance the biosynthesis of the important secondary metabolites of C. roseus. The sucrose-breaking enzyme, CWIN plays an important role in modulating various secondary metabolic pathways in the planta. There are three CWIN isoforms in C. roseus that show specific differential expression in the tissue pattern. CrCWIN2 was found to have the catalytic site required for an invertase function. Gene expression analysis is needed to outline possible correlations between expression patterns of CWIN, TIA isoforms, phenylpropanoid biosynthesis genes, sucrose metabolism genes and growth/antioxidant genes under abiotic stress conditions which are known to affect vindoline and catarantin production in C. roseus. Sucrose supplementation increases the expression of CWIN and secondary metabolic genes, levels of vindolin, catarantin, geraniol, fisetin, coumarin and cinnamic acid. The interconnection between primary and secondary metabolism is confirmed by overexpression of CrCWIN2. Keywords: Catharanthus roseus, abiotic stress, gene expression, secondary metabolite